Gene silencing of receptor-interacting protein 2 protects against cigarette smoke-induced acute lung injury. (January 2019) - Dong, Jinrui; Liao, Wupeng; Tan, Lay Hong; Yong, Amy; Peh, Wen Yan; Wong, W.S. Fred
Graphical abstract: Abstract: Background and purpose: Chronic obstructive pulmonary disease (COPD) is characterized by progressive alveolar damage and generally irreversible airflow limitation. Nuclear factor-κB (NF-κB) plays a critical role in COPD pathogenesis. Receptor-interacting protein 2 (Rip2), a 60 kDa adaptor protein, is a positive regulator of NF-κB pathway and also an inducible transcriptional product of NF-κB activation. We sought to investigate if Rip2 gene silencing could protect against cigarette smoke (CS)-induced acute lung injury. Experimental approach: Gene silencing efficacy of Rip2 siRNA was characterized in mouse macrophage and mouse lung epithelial cell lines, and in a CS-induced acute lung injury mouse model. Bronchoalveolar lavage (BAL) fluid cell counts, levels of pro-inflammatory and oxidative damage markers, lung section inflammatory and epithelium thickness scorings, and nuclear NF-κB translocation were measured. Key results: CS was found to upregulate Rip2 level in mouse lungs. Rip2 siRNA was able to suppress Rip2 levels in both macrophage and lung epithelial cell lines and in mouse lungs, block CS extract (CSE)-induced mediator release by the cultured cells, and abate neutrophil counts in BAL fluid from CS-challenged mice. Rip2 siRNA suppressed CS-induced inflammatory and oxidative damage markers, and nuclear p65 accumulation and transcriptional activation in lung tissues. Besides, Rip2 siRNA was able to disrupt CSE-induced NF-κB activation in a NF-κB reporter gene assay. Conclusions and implications: Taken together, we report for the first time that Rip2 gene silencing ameliorated CS-induced acute lung injury probably via disruption of the NF-κB activity, postulating that Rip2 may be a novel therapeutic target for COPD.